2013
DOI: 10.1039/c3sc22147d
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation of dsDNA immobilised at a negatively charged gold electrode is not caused by electrostatic repulsion

Abstract: Double-stranded DNA immobilised through a thiol anchor at a gold electrode surface can be unwound and denatured by applying a negative potential. One proposed mechanism for this electrochemical denaturation is that electrostatic field effects are responsible for the destabilisation of the dsDNA through repulsion of the DNA sugar-phosphate backbone away from the electrode surface. Herein, we demonstrate conclusively that electrochemical melting at gold electrodes cannot be explained solely as a simple repulsion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 50 publications
0
43
1
2
Order By: Relevance
“…What is important, the true nature of the observed electrochemical DNA melting is not well‐understood yet. Later experiments with mixed DNA/peptide nucleic acid (PNA) and PNA/PNA duplexes evidence that electrochemical melting of DNA cannot be explained by electrostatic repulsion of DNA from the electrode surface only, since PNA hybrids, whose backbone is not negatively charged, demonstrated a very similar to dsDNA denaturation behaviour at negative electrode potentials . Our recent in situ polarization modulation infrared reflection absorption spectroscopy studies performed under the electrochemical control show that the potential‐induced conformational changes of the electrode‐tethered DNA duplexes depend primarily on the sequence composition, and the electric field in first turn affects the mobility of the base pairs in dsDNA, not the sugar‐phosphate backbone, by this destabilizing the double helix structure .…”
Section: Electrochemical Melting Of Dsdnamentioning
confidence: 99%
“…What is important, the true nature of the observed electrochemical DNA melting is not well‐understood yet. Later experiments with mixed DNA/peptide nucleic acid (PNA) and PNA/PNA duplexes evidence that electrochemical melting of DNA cannot be explained by electrostatic repulsion of DNA from the electrode surface only, since PNA hybrids, whose backbone is not negatively charged, demonstrated a very similar to dsDNA denaturation behaviour at negative electrode potentials . Our recent in situ polarization modulation infrared reflection absorption spectroscopy studies performed under the electrochemical control show that the potential‐induced conformational changes of the electrode‐tethered DNA duplexes depend primarily on the sequence composition, and the electric field in first turn affects the mobility of the base pairs in dsDNA, not the sugar‐phosphate backbone, by this destabilizing the double helix structure .…”
Section: Electrochemical Melting Of Dsdnamentioning
confidence: 99%
“…The proposed denaturation mechanism employed electrostatic repulsion between a polarized electrode and the DNA molecules on its surface. However, electrochemical dehybridization of non‐charged PNA‐PNA hybrids suggested that the denaturation mechanism is not as straightforward as it was believed . Bartlett et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bartlett et al. showed that the so‐called DNA melting potential ( E m ) strongly depends on DNA base sequences and the ionic strength ,. Accordingly, SNP analysis was achieved by defining DNA melting potentials for a number of different oligonucleotides .…”
Section: Introductionmentioning
confidence: 99%
“…[13] So wird auch nur ein kleiner Anteil eines DNA-Strangs in der Umgebung der elektrifizierten Oberfläche vom angelegten Potential beeinflusst. [13] So wird auch nur ein kleiner Anteil eines DNA-Strangs in der Umgebung der elektrifizierten Oberfläche vom angelegten Potential beeinflusst.…”
unclassified
“…Um eine dichte Bedeckung und hohe Geschwindigkeiten zu erreichen, erfolgt die pDNA-Immobilisierung häufig in Lçsungen mit hoher Ionenstärke.D ie Debey-Länge,w elche die Abnahme des elektrischen Potentials in der Elektrolytlçsung vor der Elektrode beschreibt, verringert sich stark mit der Ionenstärke,u nd folglich ist bei hohen Ionenstärken bereits ein erheblicher Potentialabfall in der nächsten Umgebung der Elektrode zu verzeichnen. [13] So wird auch nur ein kleiner Anteil eines DNA-Strangs in der Umgebung der elektrifizierten Oberfläche vom angelegten Potential beeinflusst. DNAi st ein mehrfach negativ geladener Polyelektrolyt, der mit den in der Elektrolytlçsung vorhandenen Ionen wechselwirkt, sodass die Ladung weitestgehend kompensiert wird.…”
unclassified